If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x = x Solving 14x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 14x + -1x = x + -1x Combine like terms: 14x + -1x = 13x 13x = x + -1x Combine like terms: x + -1x = 0 13x = 0 Divide each side by '13'. x = 0 Simplifying x = 0
| 4(3)(3)+12= | | x+42=208 | | 180-(2x-4)= | | 4(x-3)+20=3(x+5) | | 2xy+3y=4x-1 | | 1200+45p=1800+60p | | 42*x=208 | | 4(10-2x)=88 | | 5T^2-200=45 | | 5y-8=10y+2 | | 2(4t+2)+t+7= | | 25-t=5 | | (3x-3)=(4x-14) | | p-7525=581600 | | 8x-2=1+7x | | -3x=-23 | | 22.5+7(n-3.4)= | | 30=7n | | 7x-10=40+2x | | 9m-14=2m | | 9z-9=-8z-1 | | 15x-(2x-9)=87 | | -(-2)+13=x | | y=7x^2+4x-4 | | 300+2x^2=62x | | 7m+14=2m | | V^3-6v^2+5v-30=0 | | 4x=(6x-23)+3 | | z=17+4x+4y | | 17-4x=-15 | | 8m+14=2m | | 2x-3-(3x+2)=-76 |